2019
DOI: 10.18632/oncotarget.26641
|View full text |Cite|
|
Sign up to set email alerts
|

A novel therapeutic approach to colorectal cancer in diabetes: role of metformin and rapamycin

Abstract: The link between colorectal cancer (CRC), diabetes mellitus (DM) and inflammation is well established, and polytherapy, including rapamycin, has been adopted. This study is a novel approach that aimed at assessing the effect of a combination therapy of metformin and rapamycin on the control or prevention of CRC in diabetic animals, in presence or absence of probiotics. Fifty NOD/SCIDs male mice developed xenograft by inoculating HCT116 cells. They were equally divided into diabetics (induced by Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Combination with IR inhibits DNA repair protein that increases radiosensitivity in HCT116 p53 − / − xenografts mice.Metformin (alone, 150 mg/kg body weight) and with rapamycin (intraperitoneal, 0.5 mg/kg body weight) modulates AMPK and mTOR modulation, inhibits tumor volume in HCT116-xenorafted NOD/SCIDs male mice. The addition of probiotic mixture inhibited the intracellular ROS, IL-3, and IL-6 levels which further reduced the tumor volume by 40%.[44, 48, 63]DMH-induced CRC in diabetic and non-diabetic miceSingle (100 or 200 mg/kg) and combination of metformin and/or oxaliplatin inhibited angiogenesis and tumor proliferation in DMH-induced CRC diabetic and non-diabetic mice by suppressing tumor angiogenesis and cell proliferation by reducing serum VEGF level and intratumoral IGFR-I.[61]PDX- female SCID miceMetformin (150 mg/kg, 24 days) suppresses tumor growth (by 50%) in PDX CRC-female SCID mice. Combination with 5-FU (IP, 25 mg/kg) inhibited tumor growth (up to 85%).…”
Section: The Preclinical Evidence Use Of Metformin In Crcmentioning
confidence: 99%
“…Combination with IR inhibits DNA repair protein that increases radiosensitivity in HCT116 p53 − / − xenografts mice.Metformin (alone, 150 mg/kg body weight) and with rapamycin (intraperitoneal, 0.5 mg/kg body weight) modulates AMPK and mTOR modulation, inhibits tumor volume in HCT116-xenorafted NOD/SCIDs male mice. The addition of probiotic mixture inhibited the intracellular ROS, IL-3, and IL-6 levels which further reduced the tumor volume by 40%.[44, 48, 63]DMH-induced CRC in diabetic and non-diabetic miceSingle (100 or 200 mg/kg) and combination of metformin and/or oxaliplatin inhibited angiogenesis and tumor proliferation in DMH-induced CRC diabetic and non-diabetic mice by suppressing tumor angiogenesis and cell proliferation by reducing serum VEGF level and intratumoral IGFR-I.[61]PDX- female SCID miceMetformin (150 mg/kg, 24 days) suppresses tumor growth (by 50%) in PDX CRC-female SCID mice. Combination with 5-FU (IP, 25 mg/kg) inhibited tumor growth (up to 85%).…”
Section: The Preclinical Evidence Use Of Metformin In Crcmentioning
confidence: 99%
“…It has also been suggested that there might be an inflammation-triggering effect of the intestinal microbiota in the development of autoimmune diabetes [ 11 , 12 ]. Previous publications from our group and others supported the possible pathogenic links among CRC and diabetes, whereby an altered glucose metabolism, an oxidative stress, and a chronic inflammatory state, triggered by an imbalance in the intestinal microbiota, are potential mediators [ 3 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 92%
“…A series of recent publications support the fact that inflammation paralleled with dysfunctional interactions between gut microbiota and the mucosal immune system are well defined risk factors for IBD, CRC, and other inflammatory and metabolic diseases such as diabetes [ 3 , 5 , 13 ]. On this basis, the recommendation of probiotics as part of the management protocols has been widely considered [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…(29) Geagea et al showed the synergetic effects of metformin and rapamycin in association with the probiotics caused to decreased expression of early lesions in CRC such as ACF in mice with xenografts. (30)…”
Section: Cellular and Pre-clinical Datamentioning
confidence: 99%